Implementation of water conservation based on drought assessment and its impact on crops by using UNEP Aridity Index - KUMAR, SUNIL (Journal of Soil and Water Conservation, 2023)
Aridity Index (UNEP AI) method was used to identify meteorological drought for long term (1990-2019) in Bundelkhand region of India. Probability of drought occurrences were calculated for different districts based on UNEP AI. Impact of drought on yield of major crops (rice and sorghum) was analyzed by using long term yield. Water conservation methods were chosen according to the frequency and probability of drought. The highest probability of occurrence for extreme drought (3.33%) was monitored in three districts Chhatarpur, Damoh and Lalitpur. The highest percentage was observed at Jalaun district as 8.00% for severe drought and of the moderate drought as 11.33% at Jhansi district. The highest probability of occurrence for hyper arid (9.33%) was monitored in Datia district and for arid category in same district as 14.00%. The highest percentage of occurrence of probability for semi-arid category was detected as 22.67% at Jalaun and Tikamgarh districts. In most of the districts yield of rice and sorghum was reduced in drought years which was also shown by aridity index, though the effect of drought was reduced due to good irrigation facility in some districts like Lalitpur. In some years it was found that rice was affected less than sorghum due to provision of irrigation in comparison to sorghum crop. By increasing irrigation frequencies and their proper management, impact of drought can be minimized which was found in some districts where good facility of irrigation was existing for crops. Accordingly, water conservation methods can be used for different districts in the region based on drought frequency and probability of drought and soils found in the region. In-situ water conservation in the field itself was found significant to improve the water availability for crops.